Two wild hybrids of Erica L. (Ericaceae) from northwest Spain - Fagúndez, Jaime (Botanica Complutensis, 2006)
Two hybrids of genus Erica L. are recorded from northwest Spain. Erica x stuartii (MacFarl.) Mast. (E. tetralix L. x E. mackaiana Bab.) is recorded from Aranga (A Coruña, NW Spain). Hitherto this hybrid was only known from Ireland and Asturias (N Spain). Erica x veitchii Bean (E. arborea L. x E. lusitanica Rudolphi) is recorded from Asturias for first time in the wild. E. lusitanica corresponds to the recently described subspecies cantabrica Fagúndez & Izco, therefore a new name for the nothosubspecies is proposed: E. x veitchii nothosubsp. Asturica nothosubsp. nov.